EXPLORING HOSPITALITY STUDENTS’ EXPECTATION FOR INTERNSHIP PLACEMENT DURING THE COVID-19 PANDEMIC: THE CASE OF UNIVERSITI UTARA MALAYSIA STUDENTS (Journal of Event, Tourism and Hospitality Studies, 2022)
The Covid-19 pandemic has impacted the tourism and hospitality industry globally and the accommodation sector is amongst the hardest-hit. As for hospitality education, the internship program is part of the core component curricula for most undergraduate degrees which provide students with the opportunity to gain hands on experience within the industry. This paper provides some insights on issues and challenges faced by hospitality students in securing internship placements during the Covid-19 period. The study utilizes qualitative research methodology using in-depth interviews. The interviews are conducted through WhatsApp voice calls and video calls and WEBEX virtual meeting platform. The findings revealed problems faced by hospitality students when securing their internship placements. This paper offers some practical suggestions for the department in charge of internship placements to be more informed about the challenges faced by the students. This is vital as acknowledging the problems will help the university become more prepared when handling internship placements during the time of pandemic. More interaction between the industry and universities as well as corporate participation in internship acceptance are crucial for the benefit of all stakeholders.